A Connecticut Yankee in King Arthur's Court - Twain, Mark, 1835-1910 (Twain, Mark, 1835-1910. Mark Twain library., 2010)
This book is designed primarily to alleviate the agony that language learning in its early stages entails, when the foreign words in the sentence simply will not combine to make sense. Legions of beginners give up when they could have made it with the aid of a book like this. But for centuries schoolmasters have frowned on this device, calling it dirty names like crib, crutch, pony. But the truth is that highly educated and motivated people have learned to read a foreign language this way. The great German archaeologist Heinrich Schliemann, who knew many ancient and modern languages, acquire.